2015
DOI: 10.1158/0008-5472.can-14-3283
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Regulation of Fate Decisions in Therapeutic T Cells to Enhance Tumor Protection and Memory Formation

Abstract: A key challenge in the field of T-cell immunotherapy for cancer is creating a suitable platform for promoting differentiation of effector cells while at the same time enabling self-renewal needed for long-term memory. Although transfer of less differentiated memory T cells increases efficacy through greater expansion and persistence in vivo, the capacity of such cells to sustain effector functions within immunosuppressive tumor microenvironments may still be limiting. We have therefore directly compared the im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…, the mammalian target of rapamycin) might augment the efficacy of adoptively transferred cells. 34 Sukumar and colleague also showed that inhibiting glycolysis promoted the formation of memory cells, and enhanced antitumor activity. 35 …”
Section: The Hostile Tumor Microenvironment: Physical and Metabolic Bmentioning
confidence: 98%
“…, the mammalian target of rapamycin) might augment the efficacy of adoptively transferred cells. 34 Sukumar and colleague also showed that inhibiting glycolysis promoted the formation of memory cells, and enhanced antitumor activity. 35 …”
Section: The Hostile Tumor Microenvironment: Physical and Metabolic Bmentioning
confidence: 98%
“…Activated mTORC1 accelerates T-cell infiltration at the tumor site and exerts more aggressive immune pressure on the growing tumors, which is associated with the prevention of tumor escape. Overexpression of PRAS40 in T cells decreases the mTORC1 signaling, promotes the T cell quiescence and blocks the tumor infiltration of the T cells in vitro and in vivo [ 68 ].…”
Section: Pras40 In Tumormentioning
confidence: 99%
“…Some studies have shown that introducing the key cell regulator-mammalian target of rapamycin (mTOR), which controls protein synthesis, is beneficial to the survival and proliferation of CAR-T cells. 30 At the same time, rat sarcoma protein homologues enriched in the brain, increased mTORC1 signal transduction, promoted the conversion to aerobic glycolysis, and increased the expansion of effector T cells.…”
Section: Immunosuppression Of Tumor Microenvironmentmentioning
confidence: 99%